The Role of PPKN Teachers in the Formation of Student Discipline at SMA Negeri 2 Binjai in the Development of Pancasila and Civic Education Subject Matter - Adlina*, Zuraidah; Hasudungan, Anju Nofarof; Nababan, Surya Aymanda (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to examine the role of PPKn teachers in the formation of student discipline at SMA Negeri 2 Binjai. This research uses qualitative research with a descriptive approach. The subjects in the study were all PPKn teachers and students who violated discipline at SMA Negeri 2 Binjai. Data collection techniques used include observation, interviews and documentation. The data analysis techniques are by reducing data, presenting data and verifying data. The results of this study show that the role of PPKn teachers in the formation of student discipline at SMA Negeri 2 Binjai, by improving discipline so that students do not commit violations, rules, and providing an understanding of discipline. As for the exemplary forms of PPKn teachers in fostering student discipline at SMA Negeri 2 Binjai, by setting good examples such as teachers must be disciplined, teachers must be responsible and teachers must be authoritative.